Work Values: A Comparative Research between Italian and Spanish Youth - Valeria Caggiano; Andrea Bellezza; Iker Omar Belsaguy; Jeronimo González-Bernal (LED Edizioni Universitarie, 2017)
A dynamic framework that is «clearly identifiable» in relation to values research (Super, 1995) is essential in order to identify the meaning of interests, motivations, attitudes and ethics (Bellotto, 2004), focused on young generations facing work world. This research aims to: identify work values and values' orientation in relation to work; specify generational and cultural differences. The research topic consists of: a sample of Spanish, composed by 230 persons, that has a more materialistic and risk-taking orientation that, even if it decreases with age, show how young Spanish are more competitive; in the Italian sample there are 203 subjects, that shows differences in terms of old and young generations regarding value orientation; the group of people from 18 to 29 years old has a significant materialistic self-orientation, definitely high if compared to the other groups. The results show the importance of work values and contribute to studies about how various groups adopt different values depending on cultural and social needs.